SEMIOTICS OF SUPERIMPOSITION, TRANSLATABILITY OF GOVERNABLE SPACES - Rouhvand, Hassan (PEOPLE: International Journal of Social Sciences, 2017)
Tales of immigrants and accounts of diaspora experience appear frequently in Jhumpa Lahiri’s Indian-American fiction. Her narratives are crowded with visual objects, all with cultural significance and spatial function. This study is a visit to the micro space of a Bengali couple in ‘This Blessed House’ of Lahiri to explore the geography of the house and the exhibitions therein; and, in the meantime, to explicate the struggles which seek to inscribe preferred meanings of the objects onto the outdoor and indoor geography of the house and to translate spatial codes into cultural language. The researcher has followed a progressive approach, as the method with the story development, to picture gradual and multilayer superimposition of foreign emblems on the homely decorations in the house and to study their function. It is unfolded at the end of the paper that the emerging relations between the mixed signs on show signify a challenge to the sole ownership of space, its governable uniformity and its axiomatic truth. The findings are thought to call into question and cast doubts about the soundness of ideological representations from diasporic experiences.